Design and implementation of intelligent question & answering system - Lau, Yi Hong (2018)
The objective of this final year project is to develop and design an Intelligent Question and Answer System which targets Student as it user. Our system will be named as NTUAsk. It is an engaging, interactive and simple system that encourage Students to ask question when they are in doubt or uncertain about anything. Students are also encouraged to try and answer questions that had been posted online to test their own knowledge. Lecturers can also participate in NTUAsk by endorsing answers or posting an answer themselves. This will not only answer the Students’ question but also boost the confidence of the Students that help answering. NTUAsk allows Student to participate with fear of shame by all giving them the ability to post anonymously. With the introduction of TEL, the interaction between Students and Lecturers will be greatly reduced, NTUAsk acts as a bridge to encourage interaction and eliminate uncertainties. The existing Q&A platform (NTULearn Discussion Board) is not interactive and has a lot of limitation which reduces the size of answering community. By constraining the participant of the discussion board to the Students that register for the module will only create “the blind leading the blind” situation. NTUAsk solves that issue by allowing all Students (including those that have already cleared the module) to participate. This web application not only increases the size of the answering community, it also increases the retention rate of Students who already cleared the module by allowing them to actively practice their knowledge. The design and development of the system consist of a Web client, RESTFul Api server and a database made use of Lucene and MySQL.